2005
DOI: 10.1627/jpi.48.358
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Binder from Asphalt Mixture Using High Temperature and High Pressure Water

Abstract: A new recycling technology is proposed for separating and recovering aggregate and binder from asphalt pavement waste to develop a sustainable asphalt pavement recycling system. Investigation of the system used water as the solvent, which is the most convenient, economic and safe solvent for humans and the environment. Hightemperature and high-pressure water was evaluated for removing the binder from the asphalt mixture and recovering the aggregate. The study found that high-temperature and high-pressure water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Past research has confirmed that high-temperature and high-pressure water can effectively remove virgin binders and efficiently recover aggregate 5) . Here we discuss the relationship between the infl uence of binder property deterioration on the conditions required for removal of binders by high-temperature and high-pressure water, and the results of high-temperature and high-pressure water reaction tests on deteriorated binders.…”
Section: Outline Of Testmentioning
confidence: 97%
See 4 more Smart Citations
“…Past research has confirmed that high-temperature and high-pressure water can effectively remove virgin binders and efficiently recover aggregate 5) . Here we discuss the relationship between the infl uence of binder property deterioration on the conditions required for removal of binders by high-temperature and high-pressure water, and the results of high-temperature and high-pressure water reaction tests on deteriorated binders.…”
Section: Outline Of Testmentioning
confidence: 97%
“…Aggregate samples after reaction were recovered by fi ltering (glass fiber filter paper with particulate retention of 1.6 µm). Solids adhering to the surface of the filter paper were removed with hexane, and the residuals and the samples were dried in a furnace (110 C for 8 h) 5) . The binder removal rate was calculated from the change in the mass of the sample before and after fi lming and reaction using Eq.…”
Section: Outline Of Testmentioning
confidence: 99%
See 3 more Smart Citations